TURN TAKING STRATEGIES AND ITS RELATIONS TO EFL LEARNERS’ PERSONALITY AND POWER IN THE INTERACTION OF ENGLISH CONVERSATION CLASS - Rohmatul Fitriyah Dewi; Suharsono Suharsono; Ahmad Munir (ETERNAL (English, Teaching, Learning and Research Journal), 2018)
Conversation is a pivotal spoken discourse needs to be practiced by EFL learners in the classroom. The successful of conversation can be achieved through turn taking strategies as the important part of the conversation. In fact, the way of EFL learners’ turn taking strategies is influenced by the social context where it is employed. This study is aimed at examining social contexts based on how EFL learners’ social personality and power influence their turn taking strategies during the interaction in English conversation class. Since this study depicts naturally occurring interaction, a qualitative approach is applied. By conducting participant observation, the data is gained from EFL learners spoken interactions by using audio recording. The findings reveal that turn taking strategy employed by the learners result their different personality. Besides, the role of power also reflects the participants’ social roles. The higher the status of participants, the more influence the language is in face-to-face interaction. In conclusion, the intertwined of language and social context is beneficial for the learners to motivate them in functioning the language.